A Biotic Support During Pregnancy to Strengthen the Gastrointestinal Performance in Puppies - Melandri, Monica; Aiudi, Giulio Guido; Caira, Michele; Alonge, Salvatore (Frontiers in Veterinary Science, 2020)
Up to 60% of neonates can be affected by gastroenteritis due to specific pathogens or aspecific polymicrobial interactions. The present study evaluated if a dietary supplementation with MOS, FOS, E. faecium and L. acidophilus in pregnancy may reduce gastroenteritis in puppies. Fifteen Great Danes were divided in 3 groups. The control group (CG) ate a standard diet. In 2 study groups, the diet was supplemented with pre- and probiotics during the last (1WG) and the last 4 pregnancy weeks (4WG). Up to 9 weeks, puppies were checked daily to identify first- or second- presentation gastroenteritis. Data were processed by χ2 (P<0.05). First-presentation gastroenteritis was more frequent in CG than in 1WG than in 4WG. Second-presentation gastroenteritis was more frequent in CG than in 1WG and 4WG. Puppies from pre- and probiotics supplemented bitches were less prone to gastroenteritis. 1WG or 4WG equally reduced second-presentation gastroenteritis in puppies, but 4WG was better than 1WG on first-presentation gastroenteritis. By entero-mammary link, supplemented bitches produced higher immune quality colostrum, thus puppies faced immunitary challenges better; moreover, maternal microbiota, positively altered by supplementation, was transferred to newborns, becoming more resistant to gastroenteritis. This information can be useful in clinical practice with the goal of preventing gastroenteritis in puppies and reducing its prevalence and severity.